Prevalence of musculoskeletal disorders among Norwegian female biathlon athletes - Østerås H; Garnæs KK; Augestad LB (Dove Medical Press, 2013)
Håvard Østerås,1 Kirsti Krohn Garnæs,2 Liv Berit Augestad3 1Department of Physical Therapy, Faculty of Health Education and Social Work, Sør-Trøndelag University College, Trondheim, Norway; 2Department of Human Movement Science, Norwegian University of Science and Technology, Trondheim, Norway; 3Department of Human Movement Science, Norwegian University of Science and Technology, Trondheim, Norway Abstract: The purpose was to examine musculoskeletal disorders in Norwegian female biathlon athletes (age ≥ 16), both juniors and seniors. The design was a retrospective cross-sectional study. In all, 148 athletes (79.1%) responded; of these, 118 athletes were 16–21 years (juniors) (77.6%), and 30 athletes were 22 years or older (seniors) (20.3%), and mean age was 19.1. A validated questionnaire was used to collect the data. The prevalence of musculoskeletal disorders was 57.8%. The most affected parts were the knee (23.0% of the total injuries), calf (12.2%), ankle/foot (10.8%), lower back (10.8%), and thigh (10.1%). The disorders resulted in training/competition cessation for 73.5% of athletes, in alternative training for 87.8%. Fifty percent of the athletes had one or several musculoskeletal disorders. Most of the problems occurred preseason, and the duration of symptoms was often prolonged. Few differences between the juniors and seniors were found. This study showed the prevalence of musculoskeletal problems among female biathlon athletes. The results indicate that prevention of lower limb problems must be prioritized, especially during the preseason. Keywords: injuries, cross-country skiing, skating